Pengembangan Sistem Pengiriman Data mengunakan LoRa Multipoint menggunakan Simple LoRa Protokol sebagai Kontrol Kebakaran Kandang Ayam - Riksa Suta Adji; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The chicken coop environment is very dangerous in the event of a fire because the materials for making chicken coops are all combustible materials, besides the location of the chicken coop which is relatively far from residential areas, so a tool is needed that can contact the owner of the cage. In the event of a fire, the cage environment does not have supporting facilities to warn the chicken coop owner so that research is implemented to assist farmers in anticipating the event of a fire. Researchers make a plan for a tool that can provide early warning when the chicken coop detects a fire by utilizing network technology in the form of a gateway that is able to manage data and a link to be distributed to smart phones. Based on the research that has been done, it can be concluded as follows, the sensor node is able to retrieve temperature and smoke data that has been designed by implementing the LM35 sensor module and the MQ-2 sensor module with the NodeMCU intermediary, the sensor node used is good enough to be used in temperature data collection. and smoke. In the process of sending data packets using the LoRa communication module, it is able to run well by running two nodes as multipoints in the process of sending data from the sensor node to the gateway. In the process of sending messages from the gateway, it has been running well, as evidenced when the gateway receives a message from the sensor node, the message will be directly forwarded to the telegram application by displaying a message that there is a fire at point one and point two. On the performance of sending data packets with the parameters of packet loss, delay and jitter, the results show that sending using variations in the distance between the sensor node and the gateway is very influential. Based on the performance test parameters, the best value is obtained at a distance of 50 meters and the bad value is at a distance of 200 meters because it is known that the value of packet loss, delay value and jitter value is greater than at a distance of 50 meters. The performance of a system by utilizing the LoRa communication protocol greatly affects the distance used, the parameter value decreases when the distance used is greater.